Differential effectiveness of the Minnesota Safe Patient Handling Act by health care setting: An exploratory study. Issue 2 (14th November 2021) - Rosebush, Christina E.; Schofield, Katherine E.; Ramirez, Marizen; Zaidman, Brian; Erickson, Darin J.; Tschida, Breca; McGovern, Patricia M.
Abstract: Background: The Minnesota Safe Patient Handling (MN SPH) Act requires health care facilities to implement comprehensive programs to protect their workers from musculoskeletal injuries caused by lifting and transferring patients. Nursing homes, hospitals, and outpatient facilities each face unique challenges implementing and maintaining SPH programs. The objective of the study was to compare patient handling injuries in these three health care settings and determine whether change in injury rate over time differed by setting following enactment of the law. Methods: Workers' compensation data from a Minnesota‐based insurer were used to describe worker and claim characteristics in nursing homes, hospitals, and outpatient facilities. Negative binomial models were used to compare claims and estimate mean annual patient handling claim rates by health care setting and time period following enactment of the law. Results: Consistent with national data, the patient handling claim rate was highest in Minnesota nursing homes (168 claims/$100 million payroll [95% confidence interval: 163–174]) followed by hospitals (35/$100 million payroll [34–37]) and outpatient facilities (2/$100 million payroll [1.8–2.2]). Patient handling claims declined by 38% over 10 years following enactment of the law (vs. 27% for all other claims). The change in claims over time did not differ by health care setting. Conclusions: In this single‐insurer sample, declines in workers' compensation claims for patient handling injuries were consistent across health care settings following enactment of a state SPH law. Though nursing homes experienced elevated claim rates overall, results suggest they are not lagging hospitals and outpatient facilities in reducing patient handling injuries.